UJI LABORATORIUM DAN ORGANOLEPTIK PADA BUBUK MPASI BERBAHAN DASAR PANGAN LOKAL UNTUK BAYI USIA 6-8 BULAN - Vedjia Medhyna; Rafika Mulia Utami (Maternal Child Health Care, 2022)
Based on the results of Riskesdas 2018, the percentage of children suffering from malnutrition and malnutrition nationally reached 17.7% in Indonesia, 13.8% of children suffered from malnutrition and 3.9% of children suffered from malnutrition. The aim of the study was to perform laboratory and organoliptic tests on local food MP - ASI powder made from potatoes, chicken liver, corn, carrots and chickpeas in infants aged 6-8 months . This research is quantitative with analytical descriptive design and experimental approach. The research was conducted in June-July 2022 at the Andalas University Laboratory . The tests carried out were laboratory and organoliptic tests . Laboratory test results show that MP-ASI contains 4.64 % carbohydrates , 10.30 % protein, 2.25 % fat , 2.45% fiber. and water level 48.32%. . The results of the organoleptic test obtained that the highest level of preference for the color of MP-ASI is 40% (like and somewhat like), the taste of MP-ASI is 40% (likes), texture of MP-ASI is 50% (likes) and the aroma of MP-ASI is 50 % (somewhat like) . So, the most content in MP-ASI is water and the highest level of preference for the texture of MP-ASI and the aroma of MP-ASI . It is expected for mothers to provide consumption of processed MP-ASI with natural ingredients in the form of vegetables and fruit without using preservatives or food flavorings so that the daily nutritional needs of babies can be fulfilled.  Keywords : Babies, MP-ASI , Local Food